Optimasi Sifat Fisik Krim dengan Variasi Asam Stearat dan Trietanolamin dalam Pembuatan Basis Krim - Amelia, Fazila; Amelia, Fitri (Departemen Kimia FMIPA UNP, 2025)
Cosmetics in cream form are more suitable. Stearic acid and triethanolamine are used as emulsifiers in making creams. The purpose of this study was to see the variation of stearic acid with triethanolamine that produces a stable cream against the physical properties of the cream preparation. The cream made was a cream with an oil-in-water (w/o) type with variations of stearic acid 5, 10, 15, 20%, and triethanolamine 2, 2.5, 3, 3.5, 4%. The heating temperature used was 400C. The cream preparation formed was evaluated through physical property testing including pH testing and Homogeneity testing and organoleptic testing. The results showed that the higher the concentration of stearic acid used, the pH of the cream decreased, but was still within the requirements of a good cream for the skin, as well as homogeneity, the higher the concentration of stearic acid, the more homogeneous the cream produced. Panelist organoleptic testing liked the color, odor and homogeneity of the 20% stearic acid variation, which was preferred by panelists. Based on the results obtained, it can be concluded that the concentration of the cream preparation with variations of stearic acid: triethanolamine 20%: 3.5% is the best preparation based on testing of physical and organoleptic properties.